STRATEGI PEMASARAN EKSPOR PALA PADA PT. GUNUNG INTAN PERMATA MANADO - Goei Gracella Valencia; Ribka M. Kumaat; Grace A. J. Rumagit (Sam Ratulangi University, 2017)
This study aims to analyze how marketing strategies implemented by PT. Gunung Intan Permata Manado in exporting the nutmeg products in order to compete with other companies. This study uses data obtanined from direct observation and interviews using questionnaires. Data analysis methods used were Matrix of Internal Factor Evaluation (IFE), Matrix of External Factor Evaluation (EFE), dan SWOT Analysis (Strengths, Weakness, Opportunities, Threats). The results showed that the marketing strategy of nutmeg export applied by PT. Gunung Intan Permata is an aggressive growth strategy (growth oriented strategy). This strategy is a profitable strategy, because the company has the power that can be used to achieve the opportunities that exist. This strategy can be implemented through several alternative strategies, namely maintaining product quality and further tightening quality control to keep nutmeg demand high and maintain product quality and corporate image to maintain good business relationships and customer loyalty.